Rhythm in Malaysian English / Anussyia a/p Muthiah - Muthiah, Anussyia (2015)
This study investigates the properties of rhythm in Malaysian English (MalE), which has been described as a syllable-timed language. However, studies have shown that instead of a binary distinction, languages can be more or less stress or syllable timed depending on factors like speaking context. This study set out to address the following questions: (1) To what extent do different speaking styles (read and informal conversational speech styles) affect the rhythmic properties found in MalE? (2) To what extent are there differences in the rhythmic properties among three ethnic groups (Malay, Chinese and Indian) in Malaysia? (3) To what extent are there differences in the rhythm of MalE based on different metrics (nPVI-V, rPVI-C and VarcoV)? The data comprised audio recordings of 12 fluent female Malaysian speakers ranging from 40-45 of age from three different ethnic groups (Malay, Chinese and Indian). The speakers were recorded in two speaking styles: reading and spontaneous speech. For each stretch of speech in both speech styles, the duration of consecutive syllables was obtained in order to derive a normalised Pairwise Variability Index (nPVI) and VarcoV. The results were compared across the three ethnic groups and between the two speaking styles. There is some evidence that the three ethnic groups were stress-timed in both read speech and spontaneous speech.